Cardiotoxicity of adjuvant chemotherapy with trastuzumab: a Japanese claim-based data analysis. Issue 2 (22nd August 2022) - Ohtsu, Hiroshi; Shimomura, Akihiko; Miyazaki, Sakiko; Yonemoto, Naohiro; Ueda, Shinichiro; Shimizu, Chikako; Sase, Kazuhiro
Abstract : Objective: Adjuvant chemotherapy with trastuzumab improves the postoperative life expectancy of women with early-stage breast cancer. Although trastuzumab is reportedly cardiotoxic, quantification based on real-world evidence is lacking. Therefore, in this study, we aimed to analyse trastuzumab cardiotoxicity using a nationwide claim-based database. Methods: In this retrospective study, we used data from a nationwide claims database (Japan Medical Data Center, Tokyo, Japan) under the universal healthcare system. Women with breast cancer who underwent initial surgery were included. Patients with recurrent or advanced-stage breast cancer, with a history of heart failure, receiving neoadjuvant chemotherapy or a preoperative history of less than 6 months were excluded. Propensity score (PS) was calculated using logistic regression based on age, cardiovascular risk factors, radiotherapy and concomitant anthracyclines (AC). Results: We identified 12 060 eligible patients (mean age 50.8±8.56 years) between January 2010 and December 2019. After 1:2 PS matching (trastuzumab users, TZ, n=1005; non-users, NT, n=2010), Cox proportional hazards model analysis showed that the rate of heart failure development within 18 months postoperative was significantly higher in the TZ group than in the NT group (adjusted HR 2.28, 95% CI 1.38 to 3.77). Baseline cardiac evaluation in the combined AC/TZ cases was 27.2% preoperative, 66.0% pre-AC and 86.6% pre-TZ, respectively. Conclusion: Trastuzumab cardiotoxicity remained relevant in the claim-based analysis adjusted for AC effects. Further collaborative studies in cardio-oncology with real-world data are warranted to improve the rate of baseline cardiovascular risk assessment in patients with cancer scheduled for cardiotoxic cancer treatment.